Stuff you should know! when you tweet on twitter? when you recycle your soda can? when you charge your iPad? - Farndon, John 1960-; Beattie, Rob (Australian Geographic, 2014)
Stuff you should know! is the fascinating story behind the daily activities we take for granted. What exactly happens when you turn on the tap, send a message on the Internet, or telephone a friend? Have you wondered where garbage goes once you've throw it out? Or where the gas that heats your home comes from? Find the answers to these questions, and many more, as you turn the pages of this book
Conceived, edited and designed by Marshall Editions, London, UK
Includes index
Keywords: Erfindung; Maschine; Alltagswissen; Technologie; Inventions / Juvenile literature; Technology / Juvenile literature; Inventions / Ouvrages pour la jeunesse; Technologie / Ouvrages pour la jeunesse; Sachbilderbuch; Kindersachbuch